Astraeus V: the emergence and evolution of metallicity scaling relations during the epoch of reionization. Issue 3 (30th November 2022) - Ucci, Graziano; Dayal, Pratika; Hutter, Anne; Kobayashi, Chiaki; Gottlöber, Stefan; Yepes, Gustavo; Hunt, Leslie; Legrand, Laurent; Tortora, Crescenzo
ABSTRACT: In this work, we have implemented a detailed physical model of galaxy chemical enrichment into the Astraeus (seminumerical rAdiative tranSfer coupling of galaxy formaTion and Reionization in N -body dark matter simUlationS) framework which couples galaxy formation and reionization in the first billion years. Simulating galaxies spanning over 2.5 orders of magnitude in halo mass with $M_{\rm h} \sim 10^{8.9}{-}10^{11.5}\, {\rm M_\odot}$ ($M_{\rm h} \sim 10^{8.9}{-}10^{12.8}\rm M_\odot$ ) at z ∼ 10 (5), we find: (i) smooth accretion of metal-poor gas from the intergalactic medium (IGM) plays a key role in diluting the interstellar medium interstellar medium metallicity which is effectively restored due to self-enrichment from star formation; (ii) a redshift averaged gas-mass loading factor that depends on the stellar mass as $η _{\rm g} ≈ 1.38 ({M_*}/{10^{10}\, {\rm \rm M_\odot }})^{-0.43}$ ; (iii) the mass–metallicity relation is already in place at z ∼ 10 and shows effectively no redshift evolution down to z ∼ 5; (iv) for a given stellar mass, the metallicity decreases with an increase in the star formation rate (SFR); (v) the key properties of the gas-phase metallicity (in units of 12 + log(O/H), stellar mass, SFR and redshift are linked through a high-redshift fundamental plane of metallicity (HFPZ) for which we provide a functional form; (vi) the mass–metallicity–SFR relations are effectively independent of the reionization radiative feedback model for $M_* {\, \, \buildrel\gt \over \sim \, \, }10^{6.5}\rm M_\odot$ galaxies; (vii) while low-mass galaxies ($M_{\rm h} {\, \, \buildrel\lt \over \sim \, \, }10^9\, \rm M_\odot$ ) are the key contributors to the metal budget of the IGM at early times, higher mass haloes provide about 50 per cent of the metal budget at lower redshifts.